Enhancing tetrafullerene based photosensors and photovoltaic cells by graphene oxide doping - Ocaya, Richard O.; Al-Hartomy, Omar A.; Dere, Aysegul; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier, 2024)
This study explores the postulated potential of tetrafullerene as a charge transport material when combined with dispersed graphene oxide (GO), over concerns about fullerene's limited performance in similar devices. Incorporating GO is expected to augment carrier concentration, increase surface area, and reduce operating voltages. Devices fabricated with p-Si/tetrafullerene with varying GO concentration exhibit notable enhancements in both dark and illuminated characteristics. The results demonstrate improved electron concentration and transport, leading to enhanced rectification ratios, ideality factors, and interface state densities across a broad bias and illumination range. Notably, devices doped with 0.2GO exhibit the most promising electrical and photoresponse characteristics, showcasing potential for applications in photosensing and photovoltaics.
Keywords: Tetrafullerene; Graphene oxide blend; Photosensor; Photovoltaic